Proxy-cryptocurrency payment system - Xiao-tong FU; Si CHEN; Ning ZHANG (Tongxin xuebao)
The decentralized cryptocurrency which was based on block chain has been thought the most successful one in history.In the system,public keys were used as the users’ accounts which guaranteed the anonymity in real transactions.However,all the transaction information was recorded in the block chain,it was a potential threat for users’ privacy which might leak the payment information.Moreover,to avoid double-spending,it was agreed that the transaction on the target block was valid only if another k blocks were generated after the target one.The long waiting time reduced the efficiency of the payment system.A model of payment system based on a proxy-cryptocurrency was proposed,and a solution based on blind signature techniques was proposed.The scheme introduced a proxy in the payment phase,by which transaction confirmation time could be reduced and the transaction efficiency could be improved.Meanwhile,the system implements better anonymity,namely as the privacy protection function.